Development of an environmental impact assessment and decision support system for seawater desalination plants : dissertation submitted in fulfilment of the requirements of the Board for Doctorates of Delft University of Technology and of the Academic Board of the UNESCO-IHE Institute for Water Education for the Degree of DOCTOR to be defended in public on Tuesday, 9 February 2010, at 10:00 hours in Delft, the Netherlands /: dissertation submitted in fulfilment of the requirements of the Board for Doctorates of Delft University of Technology and of the Academic Board of the UNESCO-IHE Institute for Water Education for the Degree of DOCTOR to be defended in public on Tuesday, 9 February 2010, at 10:00 hours in Delft, the Netherlands. (2010) - Lattemann, Sabine
No abstract available